The Role of Sports Teachers in the Formation OQWF Students’ Character - Ansori, Aang Isa; Lian, Bukman; Kristina, Putri Cicilia (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This research aimed to explore the role of sports teachers in shaping the character of students. The research method used was a literature study which involves analysis of 10 articles, books and scientific journals that are relevant to the research topic. The data was analyzed qualitatively to identify the main findings regarding the role of sports teachers in building student character. The results of the analysis show that the role of sports teachers in forming student character is very positive and has an impact. The role of a sports teacher was not only to be an instructor in terms of physical skills, but also to be a role model who inspires students to develop moral values, such as cooperation, honesty and responsibility, perseverance, fighting spirit, optimism and always upholding sportsmanship, sports activities also provide opportunities for students to learn self-control, overcome challenges, and develop discipline. In conclusion, the role of sports teachers in forming students’ character was very important and varied. Therefore, there needs to be greater attention and support for the role of sports teachers in forming student character education in schools. cooperation, honesty and responsibility. Apart from that, sports activities also provide opportunities for students to learn to control themselves, overcome challenges, and develop discipline. In conclusion, the role of sports teachers in forming the character and discipline of students is very important and varied. Therefore, there needs to be greater attention and support for the role of sports teachers in character education and student discipline in schools.